Enterprise Systems and Innovations - Benjamin Engelstätter (Verein für Socialpolitik, 2010)
This paper analyzes the relationship between the three main enterprise systems (Enterprise Resource Planning (ERP), Supply Chain Management (SCM), Customer Relationship Management (CRM)) and firms' innovational performance for process as well as product innovations. Using German firm-level data and a two part model, the results reveal that SCM systems foster the firms' likelihood of becoming a potential process innovator. In addition, ERP systems increase the number of process innovations a firm realizes. These results do not only emerge for the short-run of two years or less but remain also stable in the medium-run of two to four years. Concerning product innovational performance, only CRM systems increase the firms' likelihood to acquire product innovations, although the impact emerges for the short-run and vanishes if the long-run perspective is taken into account.
Keywords: M20; L10; O32; 330; Innovation; Product Innovation; Process Innovation; Enterprise Systems; Enterprise Resource Planning; Supply Chain Management; Customer Relationship Management